Harvesting Power from Thin Air: The Radiowave Revolution in Transforming Solar Cells into Energy Powerhouses - George Edison (BULLET : Jurnal Multidisiplin Ilmu, 2023)
In the search for sustainable energy solutions, the revolutionary potential of radio wave energy conversion has come to light as a ray of hope. This study examines the multidimensional field of radio wave energy conversion, whereby a wide range of applications, such as solar cells, wireless sensors, communication devices, etc., are powered by ambient radio waves. The journey starts with an investigation of the Radio wave Revolution, which charts the development of radio wave energy conversion from a fledgling idea to a flourishing field ready to transform energy production. Mechanisms of Radio wave Energy Harvesting explains the complex procedures involved in converting radio waves into usable power and highlights the role of rectifiers, resonant circuits, and met materials as the conversion's main building blocks. By supplying continuous radio wave-generated electricity alongside solar energy, the revolutionary marriage of radio waves with solar cells increases the efficiency and operating hours of solar energy. By combining radio wave harvesting components, improvements in radio wave-integrated photovoltaic technology increase the potential of solar cells and provide a flexible answer to problems with energy production. These integrated systems improve dependability and energy yield by utilizing the complementary powers of sunlight and radio waves. By utilizing the latent energy existing in the environment, harvesting energy from ambient radio waves can be done sustainably. In radio wave-powered solar cells, the synergy between radio waves and solar cells is investigated, revealing a range of new applications ranging from Internet of Things (IoT) devices and remote monitoring systems to healthcare and smart cities. The complexity of radio wave energy conversion are highlighted by Challenges and Opportunities, which balance efficiency optimization with potential interference issues and environmental implications. The use of radio wave energy conversion responsibly is examined in Environmental Impacts & Considerations, which weighs its advantages against issues like electromagnetic interference and material waste. In the end, improvements in efficiency, integration, material science, and wireless power transmission are anticipated in the future prospects and technological development of radio wave energy conversion. Our shared commitment to a greener and more sustainable energy future is aligned with the transformative trajectory that the convergence of interdisciplinary synergies and educational initiatives promise. This essay provides a thorough investigation of radio wave energy conversion, illuminating its potential to change energy production, reshape industries, and promote a more resilient and sustainable global community.